Republication of “Treatment of Hallux Valgus Deformity Using a Suture Button Device: A Preliminary Report” - Tyler A. Gonzalez MD, MBA; Jeremy T. Smith MD; Eric M. Bluman MD, PhD; Lauren V. Ready MPH; William Ciurylo BA; Christopher P. Chiodo MD (Foot & Ankle Orthopaedics, 2023)
Background: Hallux valgus (HV) is commonly treated with proximal or distal first metatarsal osteotomy. Despite good correction, these procedures have inherent risks such as malunion, nonunion, metatarsal shortening, loss of fixation, and avascular necrosis. Suture button fixation has been used for HV treatment. It avoids the risks of corrective osteotomies while maintaining reduction of the intermetatarsal angle (IMA). The goal of this study was to assess the radiographic and functional outcomes of patients undergoing HV correction with a distal soft tissue procedure and proximal suture button fixation. Methods: The authors retrospectively reviewed the charts and radiographs of 22 patients who had undergone HV correction using a distal soft tissue correction and proximal fixation with a miniature suture button device (Mini TightRope; Arthrex, Inc, Naples, FL). Mean follow-up was 27.7 months. The IMA, hallux valgus angle (HVA), and sesamoid station were measured on radiographs obtained preoperatively as well as in the immediate postoperative period and at final follow-up. Preoperative and postoperative Short Form-36 (SF-36) and Foot and Ankle Ability Measure (FAAM) scores were collected. Postoperative complications, and any additional operative procedures performed were also recorded. Results: The mean preoperative IMA and HVA were 16.9 and 32.6 degrees, respectively. The mean immediate postoperative IMA was 5.2 degrees ( P < .0001) and the mean HVA was 9.8 degrees ( P < .0001). At final follow-up, the mean IMA was 8.2 degrees ( P < .0001) and the mean HVA was 16.7 degrees ( P < .0001). The average change in HVA from preoperative to final follow-up was 16.0 degrees and the average change in IMA from preoperative to final follow-up was 8.6 degrees ( P < .0001). Sesamoid station assessment at the 2-week follow-up showed that 22 patients (100%) were in the normal position group; at final follow-up, 17 patients (77%) had normal position and 5 patients (23%) had displaced position. Although there were no clinically symptomatic recurrences, asymptomatic radiographic recurrence was noted in 5 patients (23%) who had a final HVA >20 degrees. All components of the FAAM and the SF-36 showed improvement from preoperative to final follow-up, although these changes were not statistically significant. Three patients experienced complications, including an intraoperative second metatarsal fracture, a postoperative second metatarsal stress fracture, and a postoperative deep vein thrombosis. Conclusion: The use of a distal soft tissue procedure in conjunction with proximal suture button fixation is a safe and effective procedure for treating symptomatic HV deformity. Our results show that this technique can correct the IMA, HVA, and sesamoid station without the need for osteotomy. Level of evidence: Level IV.